PERENCANAAN STRUKTUR RUANG DAN POLA RUANG KAWASAN EKONOMI TERPADU TERHADAP ARSITEKTUR KOTA DI KECAMATAN SEMARANG TENGAH - Wibowo, Djoko Arianto (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2025)
Central Semarang District is one of the sixteen sub-districts in Semarang City and forms the golden triangle area of Semarang City. The creation of integrated economic areas is a policy carried out by the government with the aim of reducing development gaps. The Integrated Economic Zone acts as a development engine (main engine) around the area through the availability of economic growth areas that accompany it by providing facilities that can create opportunities for the business world. This integrated economic area will ultimately give its own color to the city architecture in the central area of Semarang City. The aim of this research is to plan the architectural layout of Central Semarang District as an integrated economic area. This research uses a qualitative descriptive approach to describe the integrated economic phenomenon in the central area of Semarang City. The results of this research explain the shape and direction of spatial growth of urban architecture in Semarang City as an integrated economic area.Keywords: Spatial Structure and Spatial Pattern, Integrated Economic Zone, Urban Architecture